Effect of inclination angle on the startup of a frozen sodium heat pipe. (25th January 2022) - Ma, Yugao; Yu, Hongxing; Huang, Shanfang; Zhang, Yingnan; Liu, Yu; Wang, Chenglong; Zhong, Ruicheng; Chai, Xiaoming; Zhu, Congrong; Wang, Xueqing
Highlights: A sodium heat pipe's frozen startup at inclination is experimentally investigated. Critical startup power transits at 15°. Coupling effects of capillarity and gravity causes the startup power transition. Periodic temperature oscillations are observed at positive inclination angles. Temperature oscillations starts at about 580 ℃ and suddenly ends at about 780 ℃. The heating power and the inclination angle both affects the oscillations. Abstract: Screen-wick sodium heat pipes are highly effective passive devices for heat transport, which are mainly used in a horizontal orientation. For practical applications, the sodium heat pipe may operate at an inclination. Previous studies have mainly focused on large inclination angles where gravity dominates. By contrast, fewer experiments were conducted at a near-horizontal inclination, where neither the capillary nor gravity dominate. The coupling effects may significantly change heat pipes' startup and operation characteristics. This work experimentally investigated the temperature variations during a sodium heat pipe frozen startup at near-horizontal inclination angles, focusing on the effects of inclination angle (−15°, −10°, 0°, 5°, 10°, 15°, 30°, 45°) with a heating power of 0–1.4 kW. Various startup power regimes are identified for the various conditions. Critical startup power transits at 15° due to the competing effects of the capillary and gravitational forces. During the transient startup, the outer wall temperatures oscillated at positive inclination angles when the evaporator bottom temperature is over 580 ℃, with the oscillations suddenly stopping at 780 ℃. The inclination angle significantly affects the oscillation periods and amplitudes, which first increased and then decreased with increasing inclination angle, with peaks at 15°.